Oral hygiene and health status of rural school children in Rajahmahendravaram: a cross-sectional study - Spandana, B. Sudha; K. M., Lavanya; Mishra, Sushant Kumar; Raju S., Hari Krishnam (International Journal Of Community Medicine And Public Health, 2019)
Background: Oral health is an integral component of general health. School age, especially younger ages, is a period of overall development. Although enjoying good oral health includes more than just having healthy teeth, many children have inadequate oral and general health because of improper oral hygiene, bad eating habits etc. Oral health affects the general health, well-being, education and development of children and diminishes their quality of life. Objectives were to assess the oral health status and oral hygiene of rural school children and to determine the factors associated with it. Methods: A Community based cross-sectional study was conducted in the rural field practice area of Rajahmahendravaram for a period of 3 months. All the children between 1st to 5th classes were screened to evaluate the oral health and hygiene status. Findings were documented in a pre-validated proforma and subsequently analyzed. Results: Total 620 students were screened in 4 rural schools. About 165 (26.6%) students were 10 years age and 54.3% were boys. Decayed tooth were present in 294 (47.4%). About 17% had only 1 decayed tooth, six teeth were seen decayed among 4 (0.6%) students. Dental morbidities are seen in 509 (82.1%). Pulp involvement was seen in 11 (1.8%) students, tooth fracture in 4 (0.8%), gingival involvement in 13 (2.1%), calculus in 52 (8.4%) and scaling in 80 (12.9%). Good oral hygiene was seen in 156 (25.2%). Conclusions: Oral health status and oral hygiene among rural school children is not satisfactory and needs attention.